2014
DOI: 10.1042/bj20130915
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMACR (α-methylacyl-CoA racemase) and MFE-1 (peroxisomal multifunctional enzyme-1) in bile acid synthesis in mice

Abstract: Cholesterol is catabolized to bile acids by peroxisomal β-oxidation in which the side chain of C27-bile acid intermediates is shortened by three carbon atoms to form mature C24-bile acids. Knockout mouse models deficient in AMACR (α-methylacyl-CoA racemase) or MFE-2 (peroxisomal multifunctional enzyme type 2), in which this β-oxidation pathway is prevented, display a residual C24-bile acid pool which, although greatly reduced, implies the existence of alternative pathways of bile acid synthesis. One alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Liver weight is also increased in Amacr -/-and in double Amacr -/-/Mfp1 -/-mice [49] and, upon aging, liver tumors develop more frequently in both models. The space of Disse located between sinusoidal endothelial cells and hepatocytes was enlarged in Amacr -/-mice and disrupted in double Amacr -/-/Mfp1 -/-mice [49]. The mild pathology in Amacr -/-mice is likely due to a metabolic adaptation resulting in less intestinal cholesterol uptake and increased C27-bile acid excretion [50].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 2 more Smart Citations
“…Liver weight is also increased in Amacr -/-and in double Amacr -/-/Mfp1 -/-mice [49] and, upon aging, liver tumors develop more frequently in both models. The space of Disse located between sinusoidal endothelial cells and hepatocytes was enlarged in Amacr -/-mice and disrupted in double Amacr -/-/Mfp1 -/-mice [49]. The mild pathology in Amacr -/-mice is likely due to a metabolic adaptation resulting in less intestinal cholesterol uptake and increased C27-bile acid excretion [50].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Mice lacking ABCD3 have a twofold increased liver size but neither steatosis nor other pathologies were found [35]. Liver weight is also increased in Amacr -/-and in double Amacr -/-/Mfp1 -/-mice [49] and, upon aging, liver tumors develop more frequently in both models. The space of Disse located between sinusoidal endothelial cells and hepatocytes was enlarged in Amacr -/-mice and disrupted in double Amacr -/-/Mfp1 -/-mice [49].…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 1 more Smart Citation
“…The first Amacr deficient mouse became sick already after two weeks on the phytol diet, and within 36 weeks all of the Amacr deficient mice reached the end-point, whereas wild-type mice on the phytol diet thrived. On a standard laboratory diet that is low in α˗methyl branched fatty acids, the life span of Amacr −/− mice was comparable to wild-type controls [11]. Amacr −/− male mice seem to be more sensitive to phytol than Amacr −/− female mice based on mortality pattern ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…A difference between wild-type mouse sexes was also apparent in this study, but it seems that female Amacr−/− mice tolerated phytol better than male Amacr−/− mice. Previously it was shown that Amacr−/− mice have a normal life span on a control diet [11].…”
Section: Resultsmentioning
confidence: 99%